MEMBANGUN MASA DEPAN PENDIDIKAN INDONESIA : PROSPEK KURIKULUM MERDEKA - Isye Legita Nurholiyah; Eneng Indri Herliani; Muhamad Rifki; Mulkiyah Mulkiyah; Mutiara Jasmine Maulana; Salwa Azzahra; Endah Ratna Sonya (Yayasan Indonesia Bermutu, 2023)
Indonesia has implemented the Merdeka Curriculum, a new curricular framework designed to recover learning loss resulting from the COVID-19 pandemic and raise educational standards. The curriculum is created with a more flexible structure that places emphasis on character development and required subjects. Three categories of learning activities are included in the Independent Curriculum: extracurricular learning, intracurricular learning, and community service. Qualitative research design, a type of library research used in this research. The qualitative research design of this type of library research is research carried out using library research, which includes scientific research journals, books, notes and reports of research results that have been carried out by previous researchers. The Covid-19 pandemic in Indonesia has caused significant changes in several sectors, the education sector being the most affected. Seeing the current situation, the Ministry of Education and Culture is willing to continue the education program. One of the steps taken to overcome this problem is to change the name of the curriculum to